Interior Design Analysis Of Circulation Services In Increasing Visiting Interest In The Palembang Tourism Polytechnic Library - Amalia, Laila Rizki (Jurnal El-Pustaka, 2024)
This article discusses the effect of circulation services for library users at the Palembang Tourism Polytechnic Library. The purpose of this study was to determine the effect of circulation services at the Palembang Tourism Polytechnic Library, and also how effective circulation services at the Tourism Polytechnic Library are for users to borrow book collections in the library. Library circulation service itself is the activity of borrowing and returning book collections. This library circulation service depends on the policy of the library whether it is carried out for general borrowing or within the scope of the library itself. Library circulation services not only serve the borrowing and returning of library materials but comprehensive activities towards the process of meeting user needs through circulation services including return activities and extending the borrowing time of library materials. The research method of this article uses a qualitative descriptive type method. Qualitative descriptive research is research that describes the situation in fact as it is.  The conclusion of this article is that spatial layout and circulation services are closely related because they can influence one another to create a comfortable and attractive library to visit.